Large Area One‐Step Fabrication of Three‐Level Multiple‐Scaled Micro and Nanostructured Nickel Sleeves for Roll‐to‐Roll Hot Embossing1 . Issue 8 (12th May 2017) - Lang, Valentin; Rank, Andreas; Lasagni, Andrés F.
Abstract : Direct laser interference patterning enabled the fabrication of three level multiple‐scaled microstructures on nickel surfaces using infrared picosecond laser pulses. While the largest spatial period (1.5 to 5.7 µm) could be controlled by adjusting the angle between the interfering laser beams and the laser wavelength, low and high spatial frequency laser induced periodic surface structures with pitches of approximately 800 nm and 160 nm, respectively, were also observed. Using a set of optimized processing parameters, large area Ni‐sleeves were treated. These sleeves were later employed in preliminarily investigations of roll‐to‐roll high throughput hot‐embossing of polymer foils. Abstract : Direct Laser Interference Patterning is used to produce multiple‐scaled microstructures on nickel surfaces using picosecond laser radiation. Using this method, structure depths up to 2 µm are achieved in a one‐step process and even on the surface of large‐area Ni‐sleeves. Preliminary results on the use of the treated Ni‐sleeves for roll‐to‐roll hot embossing processing are show for the first time.